The Experience of Violence in the Lives of Elderly Women - Halicka, Małgorzata; Halicki, Jerzy (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The aim of the article is to present a part of the research done within the project: Intimate Partner Violence against Older Women. In particular, these are the opinions of the research subjects on violence and a characteristic of analyzed cases of female victims of intimate partner violence. The duration, causes and forms of aggressive behaviors are presented. An attempt is also made at characterizing the female victims of violence, who have a passive attitude towards their situation.